(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Social science research is a systematic method of exploring, analysing and conceptualising human life in order to extend, correct or verify knowledge of human behaviour and social life. In other words, Social science research “seeks to find explanations to unexplained social phenomena, to clarify the doubtful, and correct the misconceived facts of social life”. (Young Pauline .V) The aim of social science research, like research in Physical Sciences, is to discover new facts or verify and test old facts. It tries to find out the causal connection between human activities and natural laws governing them. An important purpose of the social science research is to develop new scientific tools, concepts and theories, which would facilitate reliable and valid study of human behaviour and social life. Statistics is among the most important tool used by social scientists in doing their research (Fisher, 1929). The analysis of data is the most skilled task in the research process. In this study,both quantitative and qualitative methods are used. So, social science research most often requires quantitative analysis involving the application of various statistical techniques and tools. The main objective this study is to explain the importance and role of statistics in socialscience research with special reference to relevance and significance of Correlation. The study is based on secondary data. Major finding of the study is statistical tools are played crucial role in social science research and Correlation technique is more relevant and significant in this research.